Science, Technology, Engineering, Mathematic-Based Pure Water Kit: Bibliometric Analysis on Critical Thinking and Environmental Awareness - Dewi Firta Amalia Majid; Endang Susantini; Nafisah Maulidah Rahmah; Muhammad Zahrudin Afnan; Rinaldiyanti Rukmana; Muaz Mohd Zaini Makhtar (JIPI (Jurnal IPA & Pembelajaran IPA), 2025)
Critical thinking and environmental awareness are essential 21st-century competencies that need to be developed through integrated science learning approaches. However, studies connecting water purification learning media with educational perspectives remain limited. This study seeks to delineate publication trends, prevailing research themes, and prospective future trajectories concerning the utilization of water purification media in scientific education, specifically in promoting higher-order thinking skills and environmental stewardship within the framework of Sustainable Development Goal 6. This research utilized a bibliometric analysis in accordance with the PRISMA methodology. Data were collected from the Scopus database utilizing the keyword "water purifier" for publications spanning from 2005 to 2025. Out of the 1,103 documents that were found at first, 84 publications matched the requirements for inclusion, and 40 research that were very relevant were looked at in detail. The findings indicate that research on water purification mostly emphasizes technical dimensions, like filtration efficiency and material innovation, but its incorporation into educational settings is still insufficient. These results show that there is a lot of potential for making learning materials that use water purification as a way to improve critical thinking and environmental awareness through science education that is good for the environment.